Using Server-Side Include Commands for Subject Web-Page Management: An Alternative to Database-Driven Technologies for the Smaller Academic Library - Northrup, Lori; Cherry, Ed; Darby, Della (Information Technology and Libraries, 2017)
Frustrated by the time-consuming process of updating subject Web pages, librarians at Samford University Library (SUL) developed a process for streamlining updates using Server-Side Include (SST) commands. They created text files on the library server that corresponded to each of 143 online resources. Include commands within the HTML document for each subject page refer to these text files, which are pulled into the page as it loads on the user's browser. For the user, the process is seamless. For librarians, time spent in updating Web pages is greatly reduced; changes to text files on the server result in simultaneous changes to the edited resources across the library's Web site. For small libraries with limited online resources, this process may provide an elegant solution to an ongoing problem.